EFEKTIVITAS PEMBELAJARAN JARAK JAUH DI KELAS III SD NEGERI 05 SURUH TEMBAWANG PADA MASA PANDEMI COVID-19 - Pransiska Ika; Fransisco Adam; Sukristin Sukristin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2022)
Abstract: This study aims to determine the effectiveness of distance learning in the third grade, of public elementary school 05 Suruh Tembawang during the covid-19 pandemic. The form of this research is field research with survey method (case study). The research subjects were third grade students of the third grade, of public elementary school 05 Suruh Tembawang. Data collection techniques are interview and documentation techniques. The data collection instruments were interview guides and documents. The results of the study are based on 7 indicators of distance learning effectiveness, hhey are (1) good material organization, teaching the criteria of 70% and 30% (2) effective communication, teaching the criteria of 30% and 70% (3) mastery and enthusiasm for the subject matter, 70% and 30% (4) positive attitude towards students, 30% and 26% (5) giving fair assesment, 26% and 74% (6) flexibility in learning approach, 70% and 30% (7) student learning outcomes, 30% and 70%. The conclusion is good the implementation of distance learning during the covid-19 pandemic in third grade students of the third grade, of public elementary school 05 Suruh Tembawang is not effective.Keywords: Effectiveness of Distance Learning, covid-19 pandemic